Implementasi Nilai Pendidikan Ahlak Tasawwuf melalui Program Kampus Mengajar Angkatan : (Studi Kasus di SDN Pakem Kabupaten Bondowoso) - Heryandi, M. Tubi; Surur, Afiyatus (Universitas Bondowoso, 2023)
This research discusses the 6th Class Teaching Campus Program which has the value of Tasawwuf Ahlak education as stated in the MBKM. The Teaching Campus Program, this further brings out the value of the Tassawwuf sessions in which thirteen planned programs are carried out by Bondowoso University students by combining science with Islam based on the Tassawwuf Ahlak, one of which is providing understanding and exemplifying the implementation of Tazkiyatun Nafs or self-purification in Islamic education based on Ijtihad Majid Irsan Kailani in the book Manahij Tarbiyah Islamiyah wal Murabbunal Amiluna Fiha. The type of method used is qualitative and literature review. This analysis aims to understand the meaning and objectives of Tazkiyatun Nafs as well as identifying twelve campus teaching programs for class 6 of Bondowoso University at SDN Pakem Jalan Raya Pakem, Bondowoso Regency which can be integrated into MBKM. The results show that the Class 6 Teaching Campus Program based on Tasawwuf or Tazkiyatun Nafs is important for ridding humans of mental illnesses such as tyranny and oppression, purifying Islamic culture from destructive values, and fostering the values ​​of universal brotherhood. Practically, Tazkiyatun Nafs includes four mental, spiritual and physical aspects of human material such as purification of intellectual competence, purification of will drive, sensory purification of hearing and sight and physical purification. This article recommends more integration of Tazkiyatun Nafs in the curriculum and life of Islamic education.